A THEORETICAL ANALYSIS OF SYSTEM DYNAMICS METHODOLOGY ON INFRASTRUCTURE PROJECTS WITHIN THE ENERGY SECTOR - Mashamba, Takalani; Kanakana-Katumba, Grace Mukondeleli; Maladzhi, Rendani Wilson (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2023)
The energy sector is critical to a country's economic and social development. Due to economic growth in South Africa, the state-owned firm has witnessed a demand for power supply over the last 20 years. To alleviate the existing supply restriction, it is now implementing capital expansion build programs. The completion of this project has been delayed. Over the last two decades, there has been a lot of system-based study such as considerable research that uses system dynamics (SD) as an analytical and modelling approach. However, merely limited critical reviews have been conducted to provide understanding of SD application in infrastructure projects. We summarize and analyse current research on SD models in infrastructure construction projects in the energy sector in this study, which is based on a thorough systematic literature review. Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach was used to conduct a search and only 15 studies out of 130 were found to be relevant. According to the findings of the literature analysis, four main feedback structures from prior SD project dynamics models have been recognized as major trends. Design errors, rework and change management, performance and effectiveness, resource management, and project planning and control are some of the topics covered.